Asymmetrically coordinated cobalt single atom on carbon nitride for highly selective photocatalytic oxidation of CH₄ to CH₃OH - Ding, Jie (2023)
By breaking structural symmetry of the single atomic active site, the photocatalytic water oxidation pathway is tuned for highly selective oxidation of CH4 to CH3OH in an aqueous solution. The water oxidation ability and its influence on photocatalytic oxidation of CH4 over symmetrically coordinated cobalt single atom (Co-4N) on carbon nitride (SC-Co1/PCN) and asymmetrically coordinated cobalt single atom (Co-C2N2) on carbon nitride (AC-Co1/PCNKOH) photocatalysts are systematically investigated. A super selectivity of 87.22% for photocatalytic oxidation of CH4 to CH3OH is realized on AC-Co1/PCNKOH, which is only 45% on SC-Co1/PCN. Moreover, a CH4 conversion of 2.42% and a CH3OH yield of 2.11% are achieved over AC-Co1/PCNKOH (200 mg). Combining multiple in-situ characterizations and time-dependent density functional theory calculations, it is revealed that AC-Co1/PCNKOH possesses a desired electronic configuration for single-electron transfer water oxidation reaction during photocatalysis, leading to a notably promoted selectivity for CH4 oxidation to CH3OH under illumination.